Turning Around: A Novella Exploring Escapism and Its Impacts on an Individual’s Development - Albeth Utomo; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2025)
Escapism is a universal act people have done at least once in their life. By escaping from responsibilities, they seek solace but depending on the frequency, it can become detrimental. This creative thesis explores what escapism and its impacts are that affect an individual’s development. As a novella in the genre of science fiction, this work uses Longeway’s theory of escapism, focusing on the model of self-suppression and self-expansion. This story follows Lukas, a human, and IFT-199, an alien, who are indulging in escapism in their own way. Lukas shows self-suppression through his obsession with online conspiracies and avoidance of his aspiration while IFT-199 shows self-suppression through the ignorance of her powerlessness in her act of revenge. At the end, they grow with self-expansion by finding new aspirations in life. Through their struggle, this novella shines a light on the importance of understanding escapism, especially with its characteristics.